2016
DOI: 10.3390/v8010020
|View full text |Cite
|
Sign up to set email alerts
|

Features of the Antitumor Effect of Vaccinia Virus Lister Strain

Abstract: Oncolytic abilities of vaccinia virus (VACV) served as a basis for the development of various recombinants for treating cancer; however, “natural” oncolytic properties of the virus are not examined in detail. Our study was conducted to know how the genetically unmodified L-IVP strain of VACV produces its antitumor effect. Human A431 carcinoma xenografts in nude mice and murine Ehrlich carcinoma in C57Bl mice were used as targets for VACV, which was injected intratumorally. A set of virological methods, immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Such danger signals could be sensed by cells of innate immune system, so it could be suggested that activation of innate immune system might take part in tumor regression in cooperation with the viral oncolytic process [ 45 ]. Moreover, most recently, Zonov et al demonstrated that direct cell destruction have been implicated in vaccinia infection of human carcinoma A431 cells, but in Ehrlich carcinoma cells which poorly supported vaccinia virus replication the virus induced suppression of mitoses [ 46 ]. However, nowadays the mechanisms mediating death of vaccinia virus infected cells are not clear entirely.…”
Section: Discussionmentioning
confidence: 99%
“…Such danger signals could be sensed by cells of innate immune system, so it could be suggested that activation of innate immune system might take part in tumor regression in cooperation with the viral oncolytic process [ 45 ]. Moreover, most recently, Zonov et al demonstrated that direct cell destruction have been implicated in vaccinia infection of human carcinoma A431 cells, but in Ehrlich carcinoma cells which poorly supported vaccinia virus replication the virus induced suppression of mitoses [ 46 ]. However, nowadays the mechanisms mediating death of vaccinia virus infected cells are not clear entirely.…”
Section: Discussionmentioning
confidence: 99%
“…VV-L replication in the models used in this study was likely restricted to the virus-injected tumors with limited hematogenous spread of the virus. 43 The majority of animals did not have detectable VV-L in the serum, and those that did had peak levels of less than 10 3 TCID 50 /mL, suggesting that VV-L has very limited ability to disseminate beyond the injected tumor. Although toxicities to normal tissues as a consequence of combining VV-L with RNA viruses was not observed in the studies reported here, there are several effective antiviral agents that could be administered to limit VV-L replication if toxicity were ever observed.…”
Section: Discussionmentioning
confidence: 93%
“…The L-IVP strain was used for the production of most of the vaccines donated to the Intensified Smallpox Eradication Programme after 1971 ( 3 ). Both nonrecombinant and recombinant variants of the L-IVP strain demonstrated high levels of tumor cell selectivity and oncolytic activity ( 4 6 ).…”
Section: Genome Announcementmentioning
confidence: 99%